Validitas Instrumen Soal Berbasis HOTS Berbantuan Quizizz untuk Melatih Kemampuan Pemecahan Masalah Peserta Didik Kelas X di SMA - Nila Matili; Lilan Dama; Nurul Fajryani Usman; Frida Maryati Yusuf; Syam S. Kumaji (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Learning in the 21st century demands a paradigm shift in education, including biology learning. The rapid development of technology and information has made society increasingly connected globally in the digital era. 4C skills are crucial to be applied in biology learning, as it not only focuses on learning concepts but also demands analytical skills on natural phenomena and contextual problem solving. This study aims to determine whether the development of HOTS questions using Quizizz can train students' problem-solving skills. The type of research used is ADDIE model development research. This development research procedure applies the ADDIE model, which includes five stages: 1) analyze; 2) design; 3) develop; 4) implement; and 5) evaluate. However, in this study, the process only reached the development stage and was not continued to the next stage, so the final results of the study were limited without field testing or comprehensive evaluation. The subjects of this study were grade X students of SMA Negeri 2 Wonosari. The product developed in this study was HOTS-based questions using Quizizz. The validation process was carried out by two biology lecturers who acted as material and media validators. This validation aimed to assess the feasibility of the developed HOTS quiz product, supported by Quizizz, and to obtain feedback and suggestions. The validation results showed an average score of 81% for question validation and 98% for media validation, both of which fall into the